Egg quality and cholesterol content of quail fed a combination of Golden snails (Pomacea canaliculata L.) and Azolla pinata - Lutfi, Ahmad Andi; Rahmawati, Yunita; Marty, Safrina; Wibowo, M. Faris Hertanto; Salshabilla, Keisya Okta; Wulandari, Suci; Pantaya, Dadik (Universitas Sebelas Maret, 2025)
Objective: This study aims to investigate the combined of the use of Golden snail flour (Pomacea canaliculata L.) and Azolla pinnata as sources of protein and carotene to improve the quality of quail eggs. Methods: The materials used in this study were 80 five-week-old laying quails. Golden snails and Azolla pinnata were processed into flour and then mixed with other ingredients (corn, concentrate, bran, palm oil, and premix) until they reached isoprotein and isoenergy (CP = 19% and EM = 2,900 kcal/kg). A Completely Randomized Design was employed, consisting of 4 treatments and 5 replications. Differences among results were analyzed using the Duncan Test. The treatments consisted of: T0 = Control (without Golden Snails and Azolla); T1 = Using 10% Azolla pinnata; T2 = Using 10% Golden snails; P3 = Using 10% Golden snails and 10% Azolla pinnata. The observed parameters included: 1) Egg quality which encompass egg weight, egg yolk index, egg white index, eggshell thickness, and egg yolk color; and egg yolk cholesterol content. Results: The results of the study showed that the provision of Golden snails and Azolla showed significantly different results (P